TRADISI MITOS SANGKAL DALAM PERTUNANGAN DINI PERSPEKTIF KIAI DI MADURA - Iwan Kuswandi; Lilik Fadilatin Azizah (IAIN Surakarta, 2018)
This paper aims to analyze early childhood engagement in Pragaan, Madura. In this case, the focus of his study is on the views of the kiai in the area regarding people's belief in the myth of sangkal tako’ in the tradition of early engagement. This research uses a qualitative approach, with a type of case study. The location of this study is in Pragaan District, Sumenep Regency, Madura. The results of this study indicate that the kiai in Pruruan District, agree on the tradition of early engagement in their area, not in conflict with Islamic law. However, some scholars think that the blessing of parents is a condition of engagement, and some others say that girls are free to choose a partner. Furthermore, the myth of sangkal in the tradition of early childhood engagement is considered not to violate the Islamic Shari'a and is considered a habit (al'adah).